Peritoneal dialysis related peritonitis caused by commensal neisseria species: a retrospective case series - Ying Liu; Yuan Feng; Yanting Yu; Qiuyuan Shao; Sixiu Liu; Qingyan Zhang; Chunming Jiang (BMC Nephrology)
Abstract Background Commensal Neisseria species are increasingly recognized as invasive pathogens. Neisseria peritoneal dialysis (PD) related peritonitis is extremely rare, and its clinical course remains unclear. This study aimed to provide an overview of the clinical characteristics and coutcomes of Neisseria peritonitis. Methods This single-center study retrospectively reviewed all Neisseria peritonitis episodes diagnosed from 1 January 2014 to 31 March 2024. Demographics, biochemical data and clinical outcomes were recorded. Results During this period, 433 episodes of peritonitis were recorded, 13 (3.0%) of which were caused by Neisseria species. All patients had hypoproteinemia, and 63.64% of them had diabetes. More than half of the peritonitis cases occurred in winter (7/13). N. sicca was the most common species identified. 3 episodes of peritonitis were related to contamination during exchange procedures. 8 patients achieved primary response using amikacin or ceftizoxime, 2 patients were cured by switching amikacin to ceftriaxone and 1 patient had the catheter removed due to three episodes of Neisseria peritonitis within six months. Conclusions Neisseria species can cause PD related peritonitis, and contamination during PD exchange is a plausible transmission route. Our study suggests that empirical therapy with amikacin or third-generation cephalosporins may achieve complete cure in most cases. While the overall outcome of Neisseria peritonitis is generally favorable, biofilm formation warrant special clinical attention due to potential treatment challenge.